2022
DOI: 10.1017/gmb.2022.7
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome in adult acute appendicitis

Abstract: Acute appendicitis is a common acute surgical emergency; however, the pathogenesis of adult appendicitis remains poorly understood. The microbiome is increasingly thought to play a key role in inflammatory disease of the bowel and similarly, may play a role in appendicitis. This study aimed to characterise the microbiome of adult acute appendicitis in a prospective cohort. We recruited 60 adults with acute appendicitis and 20 healthy controls. Rectal swabs were taken from each patient. After DNA extraction, 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The gut microbiota, which refers to the trillions of microorganisms that live in the human gastrointestinal tract [17], mainly includes bacteria, fungi, protozoa, archaea, and viruses [18], among which bacteria are dominant that have been implicated in various aspects of human health and disease [19], including the development of appendicitis [20].…”
Section: The Role Of Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota, which refers to the trillions of microorganisms that live in the human gastrointestinal tract [17], mainly includes bacteria, fungi, protozoa, archaea, and viruses [18], among which bacteria are dominant that have been implicated in various aspects of human health and disease [19], including the development of appendicitis [20].…”
Section: The Role Of Gut Microbiomementioning
confidence: 99%
“…Appendicitis is an inflammatory condition of the appendix, and the exact mechanism by which the gut microbiota may contribute to appendicitis is not fully understood [8], but several theories have been proposed. One theory suggests that an imbalance or dysbiosis in the gut microbiota may trigger an inflammatory response in the appendix, leading to appendicitis [20]. Studies have shown that alterations in the composition and diversity of the gut microbiota, such as a decrease in beneficial bacteria and an increase in harmful bacteria, may be associated with an increased risk of appendicitis.…”
Section: The Role Of Gut Microbiomementioning
confidence: 99%